2022
DOI: 10.1007/s11558-022-09464-2
|View full text |Cite
|
Sign up to set email alerts
|

Trade Wars and Election Interference

Abstract: In response to the Trump trade war, China, the EU, and other countries enacted politically-targeted trade retaliation (PTTR) against swing states and Republican strongholds in the United States. We argue that PTTR increases public concerns about foreign election interference and assess the effects of such retaliation across partisan affiliations. We test our predictions using a national survey experiment in the United States fielded before the 2020 election. In contrast to findings about sanctions and foreign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…For one, it is costly, for another, it was novel. Brutger et al (2023) argue that politically-targeted trade retaliation risks backfiring as both Republicans and Democrats see the use of tariffs as a form of election interference. Whether the same is true of excessive compensation remains to be seen, as the use of public funds to incidentally benefit politically is acceptable, but to do so systematically may draw the voters' ire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, it is costly, for another, it was novel. Brutger et al (2023) argue that politically-targeted trade retaliation risks backfiring as both Republicans and Democrats see the use of tariffs as a form of election interference. Whether the same is true of excessive compensation remains to be seen, as the use of public funds to incidentally benefit politically is acceptable, but to do so systematically may draw the voters' ire.…”
Section: Discussionmentioning
confidence: 99%
“…Domestically, program funds were allocated on the basis of planting decisions made prior to the trade conflict, but the overall level of funding and product composition may have been designed to address electoral and economic priorities of the Trump Administration (Jares & Malhotra, 2023). Internationally, foreign governments have used retaliatory tariffs in a way to raise the electoral cost of US protection, in this case, the US tariffs on steel, aluminum, and other products (Brutger et al, 2023;Kim & Margalit, 2021). Both introduce an identification challenge, as compensatory funds flow to electorally valuable communities.…”
Section: Introductionmentioning
confidence: 99%
“…As tariffs soared, tariffs on Chinese goods were increased up to 21% and still remain high at approximately trade as a foreign policy issue 19% as of January 2021 . These tariffs, in combination with the retaliatory tariffs emanating in response from China, have severe economic and political consequences Brutger et al, 2023). Strikingly, whilst the trade confrontation with European powers seems to have diminished, the tariffs targeting China continue to be upheld under the new Biden administration (The Economist, 2021).…”
Section: A Bilateral Approach To Trade Attitudesmentioning
confidence: 99%
“…The unilateral increase of tariffs on a range of Chinese goods by the for mer U.S. Trump administration in 2018 fundamentally threatens open-economy politics. By initiating a trade war with China, the U.S. elevation of tariffs has had important political, as well as economic, repercussions Brutger et al, 2023). The unilateral tariff increase also scathes the multilateral trading system as the U.S. prioritized aggressive protectionism rather than abiding by WTO principles.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike those 2 Fetzer and Schwarz (2021) investigated the degree to which retaliation by the USA's trade partners was politically targeted and documented that retaliatory tariffs were targeted toward areas that supported Trump in the 2016 election. Brutger et al (2021) used the concept of politically targeted trade retaliation (PTTR) and found that PTTR, enacted by many countries during the Trump trade war, increased fears of election interference in the US.…”
Section: Introductionmentioning
confidence: 99%